STUDENT CONSTRUCTION TEAMS OF STAVROPOL: THE PECULIARITIES OF APPEARANCE. (TO THE 55-TH ANNIVERSARY OF THE MOVEMENT SCT) - A. Tregubov (Гуманитарные и юридические исследования)
The article analyzes the historical conditions of occurrence of national trends 1950s - formation of the movement of student construction teams and its manifestation in the Stavropol territory.